SPIRITUALITY AS A DRIVING FORCE TO ENTREPRENEURSHIP - Jozef Richard Raco; Johanis Ohoitimur; Yulius Raton; Ronald Rachmadi (Jurnal Ledalero, 2019)
Abstract: This paper aims to explore the connection between spirituality and entrepreneurship. Spirituality is a part of theology, and it has recently become an important topic in the field of economy particularly in entrepreneurship. Spirituality strengthens the commitment of entrepreneurs to advance their businesses, to help them deal with stressful situations, to sharpen the vision of their businesses, and to motivate them in keeping their business values. Spirituality also supports the entrepreneurs in giving meaning to their work, to increase their happiness, and to make them more loyal to the organization. By having a strong spirituality, the entrepreneurs can run their businesses not only to gain profits – for themselves and others – but also to enable them to better serve the people.Keywords: spirituality, entrepreneurship, theology, business, driving force, capital